2017
DOI: 10.26656/fr.2017.6.105
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of different postharvest treatments on physico-chemical characteristics, bioactive components and microbiological quality of fresh blueberries during storage period

Abstract: In recent years, there is increasing consumption and interest in berry fruits in general and blueberries in particular due to their nutritional and health characteristics. However, blueberries are highly susceptible to microbial contamination and loss of product quality. In this study, the effects of postharvest washing treatment and cold storage (15 days) on the quality of blueberries were examined. The blueberries were treated with mineral water, aqueous chlorine dioxide, electrolyzed water and Berry Very®, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
1
3
0
1
Order By: Relevance
“…Youssef and Hussien (2020) found no significant difference in TSS, TA, and pH of acidic and ALEW treated "Valencia" oranges compared with the control samples. Similar observations were reported on "Crimson Blaze" nectarine (Belay et al, 2021), "Satsuma" orange (Shi et al, 2020), "Malvina" strawberries (Nour et al, 2021), and "Duke" blueberries (Chiabrando et al, 2017) treated with EW. With respect to vegetables, no significant changes in pH values were reported between EW treated and untreated red cabbages (Chen et al, 2018).…”
Section: Total Soluble Solids Titratable Acidity and Phsupporting
confidence: 84%
See 1 more Smart Citation
“…Youssef and Hussien (2020) found no significant difference in TSS, TA, and pH of acidic and ALEW treated "Valencia" oranges compared with the control samples. Similar observations were reported on "Crimson Blaze" nectarine (Belay et al, 2021), "Satsuma" orange (Shi et al, 2020), "Malvina" strawberries (Nour et al, 2021), and "Duke" blueberries (Chiabrando et al, 2017) treated with EW. With respect to vegetables, no significant changes in pH values were reported between EW treated and untreated red cabbages (Chen et al, 2018).…”
Section: Total Soluble Solids Titratable Acidity and Phsupporting
confidence: 84%
“…The effects of AWS on the firmness of FFVs vary in different studies due to the physicochemical properties of the AWS. According to literature, some researchers found that EW do not interact positively with the cell wall‐degrading enzymes during postharvest storage, subsequently not delaying softening and altering textural parameters of FFVs (Chiabrando et al., 2017; Liu, Wang, et al., 2021; Zhao et al., 2019). Likewise, PAW combined with mild heat treatment had no impact on firmness of grapes (Xiang et al., 2020).…”
Section: Impacts Of Activated Water Systems On Fruits and Vegetables ...mentioning
confidence: 99%
“…Proses pencucian memegang peranan penting dalam mengurangi kontaminan mikroba, yakni pada pencucian I menggunakan pada larutan klorin 100-150 ppm dan pencucian II dengan 175 ppm selama 10 menit. Hasil penelitian menunjukkan bahwa perlakuan klorin dioksida memiliki efek positif pada pengurangan pertumbuhan bakteri, khamir dan jamur pada buah dan sayuran (Chiabrando, et. al., 2017).…”
Section: Pendahuluanunclassified
“…For these reasons, the alternative to antimicrobial treatments based on the use of chemical products is physical methods of control. Such methods include the application of hot water treatments (Chiabrando and Giacalone, 2015a;Chiabrando et al, 2018), UV (Guerrero-Beltran et al, 2009), gas content (high CO 2 ) (Sanchez-Ballesta et al, 2006), hypobaric treatments (Romanazzi et al, 2001), edible coatings (Chiabrando and Giacalone, 2015b), ultrasound (Fava et al, 2011) and electrolyzed water (Chiabrando et al, 2017). A recent and safe technology under study is the use of low-temperature ionized gases (positively and negatively charged ions) at atmospheric pressure (Perni et al, 2008).…”
Section: Introductionmentioning
confidence: 99%